Case Report: Heavy metal poisoning and acute liver failure following use of a folk remedy in a child with a burn - Niu, Bei-bei; Xu, Jing-jing; Jiang, Wen-wen; Lin, Xia; Zhu, Ling-dong (Frontiers in Pediatrics, 2025)
IntroducionFolk remedies for the treatment of burns are widely used in China, often due to the belief that they can prevent scarring. However, these remedies may contain complex and unregulated ingredients that can worsen wound conditions, increase infection risk, and lead to systemic heavy metal poisoning.MethodsWe report the case of a 1-year-and-8-month-old boy with a burn injury who received treatment with a folk remedy. This treatment led to worsening wound edema and hospital admission. The child developed acute liver failure, requiring plasma exchange and surgical debridement. Laboratory analyses of blood, urine, wound samples, and the folk remedy identified high levels of heavy metals, including chromium, nickel, tin, and lead.ResultsThe toxicological risks associated with the heavy metal content in folk remedies significantly contributed to the patient's condition. Following standardized medical treatment, liver enzyme levels and coagulation function returned to normal, and the child made a full recovery after 37 days.ConclusionThis case highlights the serious health risks associated with the use of folk remedies in burn management, particularly the potential for wound aggravation and systemic heavy metal poisoning. Clinicians should maintain a high index of suspicion for heavy metal toxicity and apply early, targeted interventions. Furthermore, the optimization of treatment experience for heavy metal poisoning is crucial to improving outcomes for children affected by such exposure, and providing valuable insights for future cases.